Structural Stress Analysis of the Core Component of Harmonic Reducer - Zhang Lei; Yang Weichao; Jiang Qianqian; Wang Cheng; Huang Wei (Jixie chuandong)
Aiming at the design problem of high lifespan and high bearing capacity of flexspline,taking the fillets and generator as the research object,parametric model are performed in ANSYS by response surface method and the central composite design method is used for sampling. The stiffness and stress at three points are selected as observation objects and the influence law of each fillet parameter are obtained. The analysis results show that increasing the size of each fillet can effectively reduce the stress concentration in various places and increase the stiffness. Based on the comprehensive consideration of the stress and stiffness,the optimum structural parameters are selected. In order to increase the stiffness and improve the bearing capacity of the flexspline,the drafting feature is designed at the bottom of the flexspline,and the parameter is analyzed and optimized. The short axis radial deformation of the non-standard elliptical cam generator can be increased to reduce the stress.